Growth and Biomass Production of Double Cropping Elephantgrass Odot Variety with Inserts of Bisi-16 Maize Plant at Different Planting Density - Muhamad Muhtar; Syahrudin Syahrudin; Srisukmawati Zainudin; Syamsul Bahri (Jambura Journal of Animal Science, 2022)
Elephantgrass of the odot variety has a fast harvest period and is able to regrow quickly after defoliation. Bisi-16 maize variety has high production of biomass, crude protein and digestibility of feed. The experimental plots were arranged in a block design of latin square method at 4 treatments of planting density and 4 replications for each planting density. The planting density used for the elephantgrass variety of odot were high density (H), namely H1 = 25 cm x 25 cm (16 plants/m2 without inserting maize) as a control, and H2 = 25 cm x 25 cm (16 plants/m2) with a maize plant insert of 64 plants, Middle density (M) = 25 cm x 50 cm (8 plants/m2) with a maize plant insert of 80 plants, and Low density (L) = 50 cm x 50 cm (4 plants/m2) with a maize plant insert of 100 plants. The insertion of maize plants is 1 plant for every 10 cm of density. Both elephant grass and maize will be harvested at the age of 90 days after planting. Growth and biomass production of elephantgrass odot variety and bisi-16 maize variety increased with decreasing density and increasing insertion of maize plants from high, medium and low density. Double cropping between elephantgrass variety of Odot and maize variety of bisi-16 became an excellent blend of plants in producing forage beef cattle. Low density (50 cm x 50 cm) on elephantgrass variety of odot with insertion of 100 maize plants (1 cm/1 maize seedling) resulted in a high stocking rate as sustainable beef cattle feed.